Bayesian Constant Hazard Risk Model With A Change Point Case Of Study: The Durations Of Unemployment Of A Local Employment Agency - Hamimes, Ahmed; Benamirouche, Rachid (جامعة الوادي - University of Eloued, 2020)
The purpose of the change methods is to make statistical inferences about the position of breakpoints and about other model parameters. In this article we look at the unemployed registered with the local employment agency of Ain El Benian (January 2011-July 2013). The objective is to find the breaking point in the overall survival function represents the integration probabilities of individuals registered with this agency and in the determined period. We use the constant model of instantaneous risk which corresponds to an exponential function of survival. This breaking point represents the duration of change for an unemployed individual, which is an important element for economic analysis and comparison.
مقال
Keywords: insertion probabilities ; survival function ; constant model of instantaneous risk, point of change